Modulation of Breast Cancer Cell FASN Expression by Obesity-Related Systemic Factors. (August 2022) - McClellan, Bryan; Pham, Tommy; Harlow, Brittany; Lee, Gabby; Quach, Duan; Jolly, Christopher; Brenner, Andrew; deGraffenried, Linda
Purpose: The objective of this study is to determine the impact of exposure to obesity-related systemic factors on fatty acid synthase enzyme (FASN) expression in breast cancer cells. Methods: MCF-7 breast cancer cells were exposed to sera from patients having obesity or not having obesity and subjected to quantitative reverse transcription polymerase chain reaction (RT-qPCR). Subsequent MTT and colony-forming assays using both MCF-7 and T-47D cells exposed to sera and treated with or without FASN inhibitor, TVB-3166, were used. MCF-7 cells were then treated with insulin and the sterol regulatory element–binding protein (SREBP) processing inhibitor, betulin, prior to analysis of FASN expression by quantitative RT-qPCR and western blot. Insulin-induced SREBP-FASN promoter binding was analyzed by chromatin immunoprecipitation with an anti-SREBP antibody. Results: In response to sera exposure (body mass index [BMI] >30) there was an increase in FASN expression in breast cancer cells. Furthermore, treatment with the FASN inhibitor, TVB-3166, resulted in a decreased breast cancer cell survival and proliferation while increasing apoptosis upon sera exposure (BMI >30). Insulin-exposed MCF-7 cells exhibited an increased FASN messenger RNA and protein expression, which is abrogated upon SREBP inhibition. In addition, insulin exposure induced enhanced SREBP binding to the FASN promoter. Conclusions: Our results implicate FASN as a potential mediator of obesity-induced breast cancer aggression and a therapeutic target of patients with obesity-induced breast cancer.